Diversity of accounting practices in the extractive industries listed on London Stock Exchange: standardisation pathways - Owusu, Freeman B. (2022)
Even though extractive industries (EI) play key roles in the global economy, financial reporting of their activities has been a subject of deep controversy for some decades now. In the absence of adequate regulation, several accounting methods have evolved which are used to account for pre-development costs which has been argued to impede comparability of accounts. With comparability being one of the key qualitative characteristics of accounting information, it is surprising that much attention has not been given to the extractive project even though there has been numerous calls for standardisation of practices. In response to these calls, this study seeks to examine the extent of diversity of accounting treatments for pre-development costs among extractive companies and explore the need and pathways for standardisation. The research is underpinned by positivist research philosophy and employs quantitative methods to address the research aim and objectives. The study involves 256 extractive companies listed on the London Stock Exchange and focuses on eight pre-development cost components. Data on accounting policies and treatments of the cost components are collected from 2018 annual reports of companies and these data are used in constructing harmony and comparability indices. This research adopts the van der Tas (1988) H-index and Archer, Delvaille and McLeay (1995) disclosure-adjusted C-index to measure the level of harmony. It also uses Archer, Delvaille and McLeay (1995) decomposed C-index, van der Tas (1988) I-index and Archer and McLeay (1995) I-index to measure the extent of intra- and inter-method comparability in treatment. The results confirm the diversity of accounting methods in the industries and find that for each of the eight (8) pre-development cost components analysed, there were some diversities in treatments even among users of the same accounting method. Apart from pre-licencing costs which the study finds greater tendency for them to be fully expensed by users of the different methods, for the other cost components the most common treatment is for them to be initially capitalised pending decision. The study finds that the level of harmony among users of each of the methods as measured by the H-index ranges from low to high. However, the harmony levels as measured by the disclosure-adjusted C-index are relatively lower. Full cost users exhibit the lowest level of harmony for most of the cost components. Additionally, this study identifies geological and geophysical costs, general administrative and overhead costs, licencing and other acquisition costs, and other exploration costs as “controversial” cost components because there is less harmony in their treatments. Even though the intra-method comparability ranges between moderate to high levels, the inter-method comparabilities are rather low between pairs of different accounting methods and across all four methods. These highlight the adverse effects the choice of diverse accounting practices has on the extent of comparability in the treatment of pre-development costs. The findings underscore the need for efforts to harmonise diverse practices and to achieve standardisation in the extractive industries. For cost components identified by this study as controversial, it is recommended that clear guidance on how they should be treated are provided by the Board to reduce the exercise of discretion in their treatments.